2019
DOI: 10.33788/rcis.66.16
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Green Brand Equity in Relationship Interactions and its Impact on Brand Loyalty Autori:

Abstract: This manuscript attempts to defi ne the dimensions of green brand equity from the perspective of relationship interactions and explores their impacts on brand loyalty. Through a literature review and questionnaire-based research, this paper employs structural equation modeling to test the proposed model in a case study (green fl ooring products). The results indicate that interaction-based green brand equity is comprised of fi ve aspects of green brands: image, reciprocity, attachment, trust, and satisfaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…If the consumer is already loyal to a brand and has high engagement, then the negative news about the brand will not change the level of consumer involvement in consuming a product (Lee and Jung, 2018). Furthermore, consumer interaction with brand equity affects consumer loyalty (Gen Li et al, 2019). This is in line with Yang and Lee's opinion (2019) which found that brand personality, brand commitment and quality perception are variables that affect consumer loyalty.…”
Section: Introductionsupporting
confidence: 82%
“…If the consumer is already loyal to a brand and has high engagement, then the negative news about the brand will not change the level of consumer involvement in consuming a product (Lee and Jung, 2018). Furthermore, consumer interaction with brand equity affects consumer loyalty (Gen Li et al, 2019). This is in line with Yang and Lee's opinion (2019) which found that brand personality, brand commitment and quality perception are variables that affect consumer loyalty.…”
Section: Introductionsupporting
confidence: 82%
“…We included 33 studies published between 2006 and 2021 in the SLR, with the largest number of studies from: 2020-6 studies [24,25,77,[105][106][107], 2019-6 studies [28,29,78,79,108,109], and 2017-5 studies [31][32][33]110,111] The research was conducted in Taiwan-7 studies [24,29,76,106,109,112,113], Pakistan-5 studies [32,77,[114][115][116], Turkey-4 studies [30,31,107,110], China-3 studies [25,79,114], India-3 studies [28,108,111], and Iran-3 studies [110,117,118]. One study each was related to research conducted in the United States [119], Germany [34], Finland [115], Egypt [7], Malaysia [120], Indonesia…”
Section: General Informationmentioning
confidence: 99%
“…The GBE studies included in SLR analyzed single product categories or entire manufacturing or service industries. For example, smartphones [106], clothing [25], cosmetics [29,107], mineral water [78], personal care products [107], tissues [30,109], and flooring products [79]. Coffee has been studied both as a product and as a coffee shop chain [24,112].…”
Section: General Informationmentioning
confidence: 99%
See 2 more Smart Citations